Silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, preparation method and application thereof

CN122953993APending Publication Date: 2026-10-23SHAANXI UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611109455.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

然而,纯BFO存在两大瓶颈:其一,导带位置略高于O2/·O2-氧化还原电位,电子注入驱动力弱,·O2-产率低;其二,表面氧空位密度不足,ROS生成速率受限,抗菌活性差

Benefits of technology

本发明公开的一种银掺杂铁酸铋纳米复合压电抗菌材料的制备方法,首先构建钙钛矿型铁酸铋载体,再通过紫外光照射促进Ag+在晶格中均匀迁移,结合煅烧实现Ag+对Bi3+的原位晶格取代,避免高温煅烧引起的晶格畸变与Ag0团聚。该方法在保持铁酸铋高压电系数的同时,将Ag+以+1价形式稳定嵌入A位,形成Ag-O-Fe键并引入氧空位作为电荷补偿中心,为后续力、电和化学协同抗菌奠定结构基础。在低频机械应力激发下,材料产生内建电场驱动持续生成·OH、·O2-、1O2等多种活性氧,并与Ag+形成离子与自由基的双重协同杀菌路径,10 min内对大肠杆菌和金黄色葡萄球菌抑菌率均≥99.9%,且循环稳定性优异。整套流程无需光照、无需外加H2O2,即可在常温暗场中长期维持高效、安全、稳定的灭菌性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122953993A_ABST
    Figure CN122953993A_ABST
Patent Text Reader

Abstract

The application discloses a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material and a preparation method and application thereof, and belongs to the technical field of inorganic antibacterial materials. The method comprises the following steps: adding bismuth nitrate hexahydrate and iron nitrate hexahydrate into a KOH solution, stirring until uniform dispersion, and then performing hydrothermal reaction, cooling, solid-liquid separation, washing, and drying to obtain a bismuth ferrite nanomaterial; dispersing the bismuth ferrite nanomaterial in deionized water, adding silver nitrate, performing ultraviolet irradiation, performing solid-liquid separation, drying, and calcining to obtain the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material. Ag + is substituted to the crystal lattice of Bi 3+ , an Ag-O-Fe bond is constructed and oxygen vacancies are introduced under the premise of not destroying the perovskite skeleton, an Ag + slow-release system is formed, and high piezoelectric activity of the material is maintained. Under the excitation of low-frequency mechanical stress, the material generates a built-in electric field to continuously generate various active oxygen, and a double synergistic sterilization path is formed with Ag + , the material has high inhibition rates on escherichia coli and staphylococcus aureus, and excellent cyclic stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of inorganic antibacterial materials technology, specifically relating to silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial materials, their preparation methods, and applications. Background Technology

[0002] Antimicrobial resistance (AMR) has been listed by the World Health Organization as one of the top ten global public health threats. Traditional antibiotics and organic antimicrobial agents such as quaternary ammonium salts face the risk of inactivation due to their susceptibility to resistance. Therefore, the development of novel antimicrobial platforms that are non-antibiotic-dependent, on-demand controllable, and biosafe is urgently needed. Piezocatalysis utilizes the built-in electric field generated by materials under mechanical stress to drive the generation of reactive oxygen species (ROS). It requires no external light source or chemical initiator and can directly harvest low-frequency mechanical energy from the human body (1 Hz for walking, 0.2-0.5 Hz for respiration, and 1-2 Hz for blood flow shear), achieving all-weather antimicrobial activity. This technology has attracted widespread attention in recent years.

[0003] In recent years, photoresponsive antibacterial materials have attracted widespread attention due to their advantages such as remote controllability and spatiotemporal controllability. Chinese patent application CN116060050A uses a solvothermal method and in-situ precipitation to load silver phosphate nanoparticles onto the surface of self-assembled lanthanum cobalt oxide microspheres, forming a heterostructure. By inhibiting photogenerated electron-hole recombination at the heterostructure under photoexcitation, photocatalytic activity is enhanced. The minimum inhibitory concentrations (MICs) against *Escherichia coli* and *Staphylococcus aureus* are 0.1 mg / mL and 0.15 mg / mL, respectively, with an inhibition rate approaching 100% after 10 minutes of light irradiation. However, this material is a photoresponsive antibacterial agent, and its antibacterial performance is highly dependent on external light source irradiation (visible light). Its antibacterial efficacy significantly decreases in environments with no light or insufficient light (such as deep internal infections, nighttime, or shaded surfaces), limiting its application in all-weather or dark environments. Chinese patent application CN116212921B uses La... 3+ Etching ZIF-67 yielded a LaCoO3 / Co3O4 nanocomposite material, which was then combined with g-C3N4 via wet impregnation to form a ternary heterojunction. Under UV or visible light irradiation, the material exhibited enhanced carrier migration capabilities, with MICs of 0.8 mg / mL and 0.9 mg / mL against Escherichia coli and Staphylococcus aureus, respectively, achieving an inhibition rate of over 95% after 20 min of light irradiation. However, it also relies on UV or visible light excitation to generate reactive oxygen species (ROS) for efficient antibacterial activity, exhibiting strong photodependence; furthermore, its relatively high MIC value (>0.8 mg / mL) suggests room for improvement in antibacterial efficiency. Additionally, this material does not involve a mechanically driven antibacterial mechanism and cannot utilize the widely available low-frequency mechanical energy in the environment.

[0004] Bismuth ferrite (BiFeO3, BFO), as a typical multiferroic perovskite, has a high piezoelectric coefficient (d). 33 ≈45 pm V -1 With its narrow bandgap (≈2.1 eV), it can output a localized potential under physiological stress, sufficient to activate water and dissolved oxygen to generate ROS, and is considered one of the most promising piezoelectric antibacterial materials for clinical translation. However, pure BFO has two major bottlenecks: firstly, the conduction band position is slightly higher than O2 / ·O2. - Redox potential, weak electron injection driving force, ·O2 - The first drawback is low yield; secondly, insufficient surface oxygen vacancy density limits ROS generation rate and results in poor antibacterial activity. Introducing silver (Ag) can simultaneously improve both ROS and Ag levels. + While traditional Ag-loaded nanoparticles offer high bactericidal efficiency, they are prone to detachment and burst release, leading to cytotoxicity and shielding of active sites. 0 Aggregation reduces the piezoelectric coefficient. Therefore, how to maintain the piezoelectric activity of BFO while achieving Ag... + Lattice locking and controlled release have become key challenges that urgently need to be overcome in this field. Summary of the Invention

[0005] To overcome the shortcomings of the prior art, the present invention aims to provide silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial materials, their preparation methods, and applications, thereby solving the problem of how to achieve Ag piezoelectric activity while maintaining the high piezoelectric activity of bismuth ferrite. + The technical challenge lies in achieving lattice-level stable doping and controllable release to construct a highly efficient, safe, and long-lasting antibacterial material that does not rely on a light source and can harvest mechanical energy to achieve synergistic antibacterial action through force, electricity, and chemical means.

[0006] To achieve the above objectives, the present invention employs the following technical solution: This invention discloses a method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, comprising: adding bismuth nitrate hexahydrate and ferric nitrate hexahydrate to a KOH solution, stirring until uniformly dispersed, followed by hydrothermal reaction, cooling to room temperature, solid-liquid separation, washing, and drying to obtain bismuth ferrite nanomaterials; dispersing the bismuth ferrite nanomaterials in deionized water, adding silver nitrate, subjecting the mixture to ultraviolet irradiation, followed by solid-liquid separation, drying, and calcination to obtain the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0007] Preferably, the amount of bismuth nitrate hexahydrate added is 100~120 g / L, the amount of ferric nitrate hexahydrate added is 80~100 g / L, the concentration of KOH solution is 5~7.5 mol / L, and the amount of silver nitrate added is 1 wt%~9 wt% of the mass of bismuth ferrite nanomaterials.

[0008] Preferably, the hydrothermal reaction conditions include: hydrothermal reaction at 140~160℃ for 4~6 hours.

[0009] Preferably, the ultraviolet irradiation time is 1 to 3 hours.

[0010] Preferably, the drying conditions are: drying at 100~120℃ for 8~12 h.

[0011] Preferably, the calcination conditions are: calcination at 200~400℃ for 2~4 h.

[0012] The present invention discloses a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, which is prepared by the above-mentioned preparation method of silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0013] Preferably, the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material is a rod-shaped structure encapsulated in nanosheets, Ag + The silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, uniformly doped in the BiFeO3 lattice, has a particle size of 8~30 μm.

[0014] The application of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material disclosed in this invention in the preparation of Staphylococcus aureus antibacterial agents or Escherichia coli antibacterial agents.

[0015] The present invention discloses the application of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material in the preparation of medical protective materials, antibacterial coatings or water purification materials.

[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention discloses a method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material. First, a perovskite-type bismuth ferrite support is constructed, and then Ag is promoted by ultraviolet light irradiation. + Ag migrates uniformly within the crystal lattice, and is then calcined to achieve uniform migration. + Compare 3+ In-situ lattice substitution avoids lattice distortion and Ag caused by high-temperature calcination. 0 Aggregation. This method, while maintaining the high voltage coefficient of bismuth ferrite, incorporates Ag... + The material stably embeds itself at the A-site with a +1 valence, forming an Ag-O-Fe bond and introducing oxygen vacancies as charge compensation centers, laying the structural foundation for subsequent synergistic mechanical, electrical, and chemical antibacterial action. Under low-frequency mechanical stress excitation, the material generates a built-in electric field that drives the continuous generation of ·OH and ·O2. - , 1 O2 and other reactive oxygen species, and react with Ag + It forms a dual synergistic bactericidal pathway of ions and free radicals, achieving an inhibition rate of ≥99.9% against Escherichia coli and Staphylococcus aureus within 10 minutes, with excellent cycle stability. The entire process requires no light or external H2O2, and can maintain efficient, safe, and stable sterilization performance for a long time in a dark environment at room temperature.

[0017] This invention discloses a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, wherein Ag is present in the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material. + To replace Bi 3+ Method of entering the lattice ( Figure 1 XRD without Ag 0 Peaks), forming Ag-O-Fe bonds and inducing oxygen vacancy generation, thereby constructing a high-voltage electroactive structure with Ag without destroying the perovskite framework. + Sustained-release system. As verified by examples, this material can generate a piezoelectric built-in electric field under mechanical stress, driving electron-hole separation to generate ·OH and ·O2. - , 1 O2 and other ROS, while Ag + Controllable migration from the crystal lattice enables dual sterilization by ions and free radicals. Test data shows that 10 mg / mL of the material, treated with mechanical force for 10 min, effectively inhibits Staphylococcus aureus (Staphylococcus aureus). Figure 7 ) and Escherichia coli ( Figure 11 The antibacterial rate reached 100%, and the antibacterial rate remained >90% after 10 cycles, proving that the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material prepared in this invention has the advantages of high efficiency, long-lasting effect and stability.

[0018] This invention discloses the application of a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material in the preparation of Staphylococcus aureus or Escherichia coli antibacterial agents. Without mechanical force, 10 μg / mL of the silver-doped material exhibits antibacterial activity against Staphylococcus aureus (…). Figure 6 ) and Escherichia coli ( Figure 10 It has shown a significant inhibitory effect, with significantly fewer colonies than the pure bismuth ferrite treatment group ( Figure 5 , 9 After adding mechanical force (ultrasound), the same concentration of material was treated for 10 min, and Staphylococcus aureus (…) Figure 7 ) and Escherichia coli ( Figure 11 The bacterial colonies completely disappeared, achieving a 100% antibacterial rate. This is because mechanical stress excites the piezoelectric effect of the material, driving the efficient generation of ROS through a built-in electric field, while Ag... + It can be controlled to release from the crystal lattice, synergistically destroying bacterial cell membranes, inducing lipid peroxidation, and interfering with intracellular metabolism. It exhibits broad-spectrum and highly efficient killing ability against both Staphylococcus aureus with thick cell walls and Escherichia coli with thin cell walls, overcoming the problems of high selectivity and easy drug resistance of traditional antibacterial agents.

[0019] This invention discloses the application of a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material in the preparation of medical protective materials, antibacterial coatings, or water purification materials. In medical protection, the material can automatically activate its antibacterial function using the low-frequency mechanical energy generated by daily human activities (walking, breathing, blood flow), requiring no external energy source, and is suitable for wound dressings, surgical instrument coatings, etc. In antibacterial coatings, the material can be coated on the surfaces of public facilities and medical devices, continuously inhibiting bacteria through the mechanical stress generated by daily contact and friction, reducing the use of chemical disinfectants. In water purification, the material can efficiently kill pathogens in water under dynamic conditions using water flow shear force or ultrasonic equipment, avoiding secondary pollution. In the embodiments, the material maintains a >90% antibacterial rate after 10 cycles of use, and the preparation process is simple, low-cost, and environmentally friendly, possessing the potential for large-scale production and multi-scenario application, providing a safe, intelligent, and sustainable new strategy for the control of drug-resistant bacteria. Attached Figure Description

[0020] Figure 1 The bismuth ferrite nanomaterials (BiFeO3) prepared in Comparative Example 1 of this invention and the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material (Ag) prepared in Example 1 of this invention are examples of the bismuth ferrite nanomaterials (BiFeO3) prepared in Comparative Example 1 of this invention. x Bi 1-x XRD pattern of FeO3; Figure 2 SEM image of bismuth ferrite nanomaterials prepared in Comparative Example 1; Figure 3 SEM image of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material prepared in Example 1; Figure 4 Photographs of untreated Staphylococcus aureus colony growth; Figure 5 A photograph of Staphylococcus aureus colony growth after treatment with bismuth ferrite nanomaterials prepared in Comparative Example 1. Figure 6 Photographs of Staphylococcus aureus colonies after treatment with the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material prepared in Example 1; Figure 7 Photographs of Staphylococcus aureus colony growth after treatment with silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material under applied mechanical force; Figure 8 Photographs of untreated E. coli colony growth; Figure 9 Photographs of Escherichia coli colonies after treatment with bismuth ferrite nanomaterials prepared in Comparative Example 1; Figure 10 Photographs of Escherichia coli colony growth after treatment with the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material prepared in Example 1; Figure 11This is a photograph of Escherichia coli colony growth after treatment with silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material under applied mechanical force. Detailed Implementation

[0021] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined to form new technical solutions.

[0023] Unless otherwise specified, all the technical features and preferred features mentioned herein can be combined to form new technical solutions.

[0024] In this invention, unless otherwise specified, percentage (%) or parts refer to weight percentage or parts relative to the composition.

[0025] Unless otherwise specified, the components or preferred components involved in this invention can be combined with each other to form new technical solutions.

[0026] In this invention, unless otherwise specified, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "6~22" indicates that all real numbers between "6~22" have been listed in this document, and "6~22" is simply a shortened representation of these numerical combinations.

[0027] The "scope" disclosed in this invention can be in the form of a lower limit and an upper limit, and can be one or more lower limits and one or more upper limits, respectively.

[0028] In this invention, the term "and / or" as used herein refers to any combination of one or more of the associated listed items, as well as all possible combinations, and includes such combinations.

[0029] In this invention, unless otherwise stated, the various reactions or operation steps may be performed sequentially or in a particular order. Preferably, the reaction methods described herein are performed sequentially.

[0030] Unless otherwise stated, the technical and scientific terms used herein have the same meanings as those familiar to those skilled in the art. Furthermore, any methods or materials similar to or equivalent to those described herein may also be used in this invention.

[0031] The purpose of this invention is to provide a rod-shaped silver-doped bismuth ferrite (Ag) encapsulated in nanosheets prepared by hydrothermal-photoreduction. x Bi 1-x FeO3) piezoelectric composite antibacterial material, Ag + To replace Bi 3+ Uniformly entering the lattice, inducing Fe 3+ →Fe 4+ The strength of the Bi-O bond increases; oxygen vacancies act as charge compensation centers; the material can trigger the piezoelectric effect under mechanical stress, continuously generating ·OH and ·O2. - , 1 O2 and other ROS can be released in a controlled manner, along with Ag. + This material achieves synergistic antibacterial action through a combination of mechanical, electrical, and chemical processes, achieving an inhibition rate of ≥99.9% within 10 minutes. Its preparation process is simple, low-cost, and environmentally friendly, making it applicable to fields such as medical protection, antibacterial coatings, wearable devices, and water treatment, providing a safe, efficient, and sustainable new strategy for controlling drug-resistant bacteria.

[0032] This invention employs a hydrothermal-photoreduction process to synthesize silver-doped bismuth ferrite (Ag). x Bi 1-x The FeO3 piezoelectric composite antibacterial material is prepared using perovskite-type bismuth ferrite as a carrier. Silver ions are uniformly fixed in the framework in a +1 valence state through in-situ lattice substitution. The Bi in the lattice... 3+ Ag + Precise replacement, while introducing oxygen vacancies to maintain charge balance, forms Ag. x Bi 1-x Novel structure of FeO3. Ag x Bi 1-x In FeO3, x = 0.01, 0.03, 0.05, 0.07 or 0.09.

[0033] This invention discloses a method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, comprising the following steps: Step 1: First, weigh 4.85~7.275g of bismuth nitrate hexahydrate and 4.04~6.06g of ferric nitrate hexahydrate, add them to a 5~7.5mol / L KOH solution, and stir until the solution is evenly dispersed. Then, transfer the solution to a polytetrafluoroethylene reactor and perform a hydrothermal reaction at 140~160℃ for 4~6h. After the reaction cools to room temperature, filter, wash, and centrifuge the solid precipitate in the reactor. Dry the obtained solid at 100~120℃ for 8~12h to obtain bismuth ferrite nanomaterials. The amount of bismuth nitrate hexahydrate added is 100~120 g / L; the amount of ferric nitrate hexahydrate added is 80~100 g / L.

[0034] Step 2: Weigh 0.1~0.5g of the bismuth ferrite nanomaterials obtained above, disperse them in deionized water and stir continuously; then, add silver nitrate, the amount of silver nitrate added is 1~9 wt% (based on the theoretical yield of BiFeO3), irradiate under ultraviolet light for 1~3 h, centrifuge the resulting solution and dry it at 100~120℃ for 8~12 h, take the solid and calcine it at 200~400℃ for 2~4 h to obtain the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0035] The silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material is a rod-shaped structure wrapped in nanosheets. Ag is uniformly doped in BiFeO3 lattice with a +1 valence, with abundant pores and a particle size of 8~30 μm.

[0036] An application of a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material with broad-spectrum antibacterial properties. Specifically, this material is applied in the field of antibacterial agents and can effectively kill pathogens such as Escherichia coli and Staphylococcus aureus.

[0037] This invention achieves Ag reduction under relatively mild conditions through a one-step hydrothermal-photoreduction process. + Lattice-level doping avoids lattice distortion and Ag2 damage caused by high-temperature calcination. 0 Ag ag was synthesized by combining nanosheets to maintain the high voltage performance of BFO while constructing a rod-like structure. x Bi 1-x FeO3 composite materials. Simultaneously, a synergistic antibacterial system combining mechanical, electric, and chemical processes is constructed: low-frequency mechanical stress excites Ag... x Bi 1-x The piezoelectric potential of FeO3 continuously generates reactive oxygen species under the drive of the built-in electric field, while Ag... + Confined and slow-released, Ag forms a dual attack with ROS, rapidly damaging membrane structure and intracellular metabolism; + The trace amounts of leaching further disrupt the bacterial respiratory chain, enhancing the broad-spectrum bactericidal effect. This technology employs a one-step hydrothermal-low-temperature calcination process, which is simple, low-cost, and provides a safe, intelligent, and sustainable new strategy for the control of drug-resistant bacteria.

[0038] This invention constructs Ag via a hydrothermal-photoreduction method. x Bi 1-x FeO3 rod-like structure, Ag + Ionic radius and Bi³ + Similarly, it can enter the A site without destroying the perovskite framework to form Ag-O-Fe bonds, inducing Fe³⁺. + →Fe 4+ The transformation and increased Bi-O bond strength; simultaneously, the introduction of oxygen vacancies as charge compensation centers significantly enhances ROS generation capability. Furthermore, the rod-like structure facilitates ROS generation and Ag... + Release provides abundant active sites; forms stable Ag+ A sustained-release system enhances the long-lasting antibacterial function of the material. Under mechanical stress, Ag... x Bi 1-x FeO3 generates an internal electric field, driving electron-hole separation and activating water and dissolved oxygen to generate ·OH and ·O2. - ¹O2 and other ROS; at the same time, the piezoelectric field promotes Ag + Controllable migration from the crystal lattice forms a dual bactericidal pathway of "ions-free radicals," achieving an inhibition rate of ≥99.9% against both *Escherichia coli* and *Staphylococcus aureus* within 10 minutes. It exhibits excellent cyclic stability, maintaining an antibacterial rate of over 90% after 10 cycles. The preparation process is simple, low-cost, and environmentally friendly, making it suitable for large-scale industrial production. It possesses highly efficient, safe, and sustainable antibacterial properties.

[0039] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. The components of the embodiments of the present invention described and shown in the accompanying drawings can generally be arranged and designed in various different configurations. Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0040] Example 1 A method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material includes the following steps: Step 1: First, weigh 5.8208 g of bismuth nitrate hexahydrate and 4.8480 g of ferric nitrate hexahydrate, add them to 60 mL of 6 mol / L KOH solution, and stir for 2 h until the solution is evenly dispersed; then, transfer the solution to a polytetrafluoroethylene reactor and react at 160℃ for 6 h. After the reaction is cooled to room temperature, filter, wash, and centrifuge the solid precipitate in the reactor, and dry the obtained solid at 105℃ to obtain bismuth ferrite nanomaterials. Step 2: Weigh 0.20 g of bismuth ferrite and 0.0118 g of silver nitrate, disperse them in deionized water and stir continuously. Irradiate under ultraviolet light for 2 h, dry the resulting solution at 105℃, and calcine the solid at 400℃ for 2 h to obtain silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0041] Example 2 A method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material includes the following steps: Step 1: First, weigh 5.8208 g of bismuth nitrate hexahydrate and 4.8480 g of ferric nitrate hexahydrate, add them to 60 mL of 6 mol / L KOH solution, and stir for 2 h until the solution is evenly dispersed; then, transfer the solution to a polytetrafluoroethylene reactor and react at 160℃ for 4 h. After the reaction is cooled to room temperature, filter, wash, and centrifuge the solid precipitate in the reactor, and dry the obtained solid at 105℃ to obtain bismuth ferrite nanomaterials. Step 2: Weigh 0.20 g of bismuth ferrite and 0.0118 g of silver nitrate, disperse them in deionized water and stir continuously. Irradiate under ultraviolet light for 1 h, dry the resulting solution at 105℃, and calcine the solid at 400℃ for 2 h to obtain silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0042] Example 3 A method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material includes the following steps: Step 1: First, weigh 5.8208 g of bismuth nitrate hexahydrate and 4.8480 g of ferric nitrate hexahydrate, add them to 60 mL of 6 mol / L KOH solution, and stir for 2 h until the solution is evenly dispersed; then, transfer the solution to a polytetrafluoroethylene reactor and react at 160℃ for 6 h. After the reaction is cooled to room temperature, filter, wash, and centrifuge the solid precipitate in the reactor, and dry the obtained solid at 105℃ to obtain bismuth ferrite nanomaterials. Step 2: Weigh 0.20 g of bismuth ferrite and 0.0039 g of silver nitrate, disperse them in deionized water and stir continuously. Irradiate under ultraviolet light for 2 h, dry the resulting solution at 105℃, and calcine the solid at 400℃ for 3 h to obtain silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0043] Example 4 A method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material includes the following steps: Step 1: First, weigh 5.8208 g of bismuth nitrate hexahydrate and 4.8480 g of ferric nitrate hexahydrate, add them to 60 mL of 6 mol / L KOH solution, and stir for 2 h until the solution is evenly dispersed; then, transfer the solution to a polytetrafluoroethylene reactor and react at 160℃ for 6 h. After the reaction is cooled to room temperature, filter, wash, and centrifuge the solid precipitate in the reactor, and dry the obtained solid at 105℃ to obtain bismuth ferrite nanomaterials. Step 2: Weigh 0.20 g of bismuth ferrite and 0.0118 g of silver nitrate, disperse them in deionized water and stir continuously. Irradiate under ultraviolet light for 2 h, dry the resulting solution at 105℃, and calcine the solid at 400℃ for 3 h to obtain the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0044] Example 5 A method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material includes the following steps: Step 1: Weigh 6.0000 g of bismuth nitrate hexahydrate and 4.8480 g of ferric nitrate hexahydrate, add them to 60 mL of 6 mol / L KOH solution, and stir for 2 h until the solution is evenly dispersed; then, transfer the solution to a polytetrafluoroethylene reactor and react at 140℃ for 5 h. After the reaction is cooled to room temperature, filter, wash, and centrifuge the solid precipitate in the reactor, and dry the obtained solid at 100℃ for 8 h to obtain bismuth ferrite nanomaterials. Step 2: Weigh 0.10 g of bismuth ferrite and 0.0018 g of silver nitrate (based on the theoretical yield of bismuth ferrite, the amount of silver nitrate added is 1 wt%), disperse them in deionized water and stir continuously, irradiate under ultraviolet light for 3 h, dry the resulting solution at 100℃ for 8 h, and calcine the solid at 200℃ for 4 h to obtain the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0045] Example 6 A method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material includes the following steps: Step 1: Weigh 5.8208 g of bismuth nitrate hexahydrate and 4.8480 g of ferric nitrate hexahydrate, respectively, and add them to 60 mL of 7.5 mol / L KOH solution. Stir for 2 h until the solution is evenly dispersed. Then, transfer the solution to a polytetrafluoroethylene reactor and react at 150℃ for 5 h. After the reaction is cooled to room temperature, filter, wash, and centrifuge the solid precipitate in the reactor. Dry the obtained solid at 120℃ for 12 h to obtain bismuth ferrite nanomaterials. Step 2: Weigh 0.50 g of bismuth ferrite and 0.0450 g of silver nitrate (based on the theoretical yield of bismuth ferrite, the amount of silver nitrate added is 9 wt%), disperse them in deionized water and stir continuously. Irradiate under ultraviolet light for 3 h, dry the resulting solution at 120℃ for 12 h, and calcine the solid at 300℃ for 4 h to obtain the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0046] Example 7 A method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material includes the following steps: Step 1: Weigh 7.2000 g of bismuth nitrate hexahydrate and 6.0000 g of ferric nitrate hexahydrate, add them to 60 mL of 6 mol / L KOH solution, and stir for 2 h until the solution is evenly dispersed; then, transfer the solution to a polytetrafluoroethylene reactor and react at 160℃ for 6 h. After the reaction is cooled to room temperature, filter, wash, and centrifuge the solid precipitate in the reactor, and dry the obtained solid at 105℃ for 12 h to obtain bismuth ferrite nanomaterials. Step 2: Weigh 0.20 g of bismuth ferrite and 0.0118 g of silver nitrate, disperse them in deionized water and stir continuously. Irradiate under ultraviolet light for 2 h, dry the resulting solution at 105℃ for 12 h, and calcine the solid at 400℃ for 2 h to obtain silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

[0047] Comparative Example 1 A method for preparing bismuth ferrite nanomaterials includes the following steps: Step 1: First, weigh 5.8208 g of bismuth nitrate hexahydrate and 4.8480 g of ferric nitrate hexahydrate, add them to 60 mL of 6 mol / L KOH solution, and stir for 2 h until the solution is evenly dispersed; then, transfer the solution to a polytetrafluoroethylene reactor and react at 160 °C for 6 h. After the reaction is cooled to room temperature, filter, wash, and centrifuge the solid precipitate in the reactor, and dry the obtained solid at 105 °C to obtain bismuth ferrite nanomaterials.

[0048] Figure 1 The bismuth ferrite nanomaterials (BiFeO3) prepared in Comparative Example 1 of this invention and the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material (Ag) prepared in Example 1 of this invention are examples of the bismuth ferrite nanomaterials (BiFeO3) prepared in Comparative Example 1 of this invention. x Bi 1-x The XRD pattern of BiFeO3 shows that after Ag doping, the characteristic peaks of BiFeO3 are completely preserved without any impurity peaks, indicating that Ag has been successfully doped into the crystal lattice and the main crystal phase remains unchanged. The absence of Ag2O impurity peaks proves that the doping is uniform and the material has high purity, providing structural support for the subsequent improvement of piezoelectric and antibacterial properties.

[0049] Figure 2 SEM image of bismuth ferrite nanomaterials prepared in Comparative Example 1; Figure 3 SEM images of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material prepared in Example 1; from Figure 2 and Figure 3It can be seen that bismuth ferrite exhibits an irregularly shaped rod-like structure with a relatively smooth surface, accompanied by a few rough protrusions. The particles are relatively large and show a certain degree of agglomeration. This agglomeration may be due to the strong inter-particle interaction forces during the preparation of bismuth ferrite. Furthermore, the rod-like structure has uneven thickness, with a thicker central portion, which may affect the catalytic performance of the material, and consequently, its antibacterial properties. Figure 3 The silver-doped bismuth ferrite particles exhibit a rough surface, contrasting with the bismuth ferrite sample surface, which displays a petal-like lamellar structure. The particles, with a size of approximately 5-30 μm, have a relatively rough surface. Numerous nanoscale protrusions and pores are present on the sample surface, likely formed during crystal growth after silver doping. These petal-like structures increase the specific surface area of ​​the material, contributing to improved transport, diffusion, and catalytic performance. This further demonstrates the successful preparation of the silver-doped bismuth ferrite nanocomposite antibacterial agent.

[0050] Figure 4 Photographs of untreated Staphylococcus aureus colony growth; Figure 5 A photograph of Staphylococcus aureus colony growth after treatment with bismuth ferrite nanomaterials prepared in Comparative Example 1. Figure 6 Photographs of Staphylococcus aureus colonies after treatment with the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material prepared in Example 1; Figure 7 This image shows the colony growth of Staphylococcus aureus after treatment with a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material under applied mechanical force. Figure 4 Compared with the blank control group, Figure 5 Bismuth ferrite at a concentration of 10 μg / ml has a certain inhibitory effect on Staphylococcus aureus colonies. Figure 6 After treatment with 10 μg / ml silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material for 10 min, a small number of Staphylococcus aureus colonies appeared. Figure 7 No Staphylococcus aureus colonies appeared after the addition of 10 μg / ml silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material to ultrasonic mechanical force treatment for 10 min.

[0051] Figure 8 Photographs of untreated E. coli colony growth; Figure 9 Photographs of Escherichia coli colonies after treatment with bismuth ferrite nanomaterials prepared in Comparative Example 1; Figure 10 Photographs of Escherichia coli colony growth after treatment with the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material prepared in Example 1; Figure 11 This image shows the colony growth of *E. coli* after treatment with a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material under applied mechanical force. Figure 8 Compared with the blank control group, Figure 9 Bismuth ferrite at a concentration of 10 μg / ml has a certain inhibitory effect on Escherichia coli colonies. Figure 10 After treatment with 10 μg / ml silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material for 10 min, a small number of Escherichia coli colonies appeared. Figure 11 No Escherichia coli colonies were observed after the 10 μg / ml silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material was treated with ultrasonic mechanical force for 10 min.

[0052] The results of the above embodiments show that Ag x Bi 1-x FeO3 nanocomposite piezoelectric antibacterial materials can activate a synergistic effect of mechano-electro-chemical reaction under mechanical force, in Ag + Based on controlled release, it continuously generates reactive oxygen species, synergistically providing high-density antibacterial active substances, exhibiting significant disinfection advantages against a broad spectrum of pathogens. The sterilization process eliminates dependence on near-infrared light and H2O2, and sterilization can be completed rapidly even in the dark at room temperature. Furthermore, the material preparation route is simple, the raw materials are readily available, and it has the potential for large-scale production, making it applicable to multiple scenarios such as medical protection, antibacterial coatings, and water purification.

[0053] In summary, the core of this invention, concerning the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, its preparation method, and its application, lies in the preparation method and application of a rod-shaped piezoelectric composite antibacterial material in which silver ions are in situ doped within the bismuth ferrite lattice. This method employs a hydrothermal-photoreduction process to synthesize silver-doped bismuth ferrite (Ag... x Bi 1-x The FeO3 piezoelectric composite antibacterial material is prepared using perovskite-type bismuth ferrite as a carrier. Silver ions are uniformly fixed in the framework in a +1 valence state through in-situ lattice substitution. The Bi in the lattice... 3+ Ag + Precise replacement, while introducing oxygen vacancies to maintain charge balance, forms Ag. x Bi 1-x A novel FeO3 structure. This structure can trigger a piezoelectric response under weak mechanical stimulation, instantly generating reactive oxygen species (ROS) and simultaneously releasing silver ions at extremely low doses, achieving a triple sterilization mechanism of "mechanical-electro-chemical". The entire process requires no light or external H2O2 and can maintain highly efficient, safe, and stable sterilization performance for a long time in a dark environment at room temperature.

[0054] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, characterized in that, include: Bismuth nitrate hexahydrate and ferric nitrate hexahydrate were added to KOH solution and stirred until uniformly dispersed. After hydrothermal reaction, cooling to room temperature, solid-liquid separation, washing, and drying, bismuth ferrite nanomaterials were obtained. The bismuth ferrite nanomaterials were dispersed in deionized water, silver nitrate was added, and after ultraviolet irradiation, solid-liquid separation, drying, and calcination were performed to obtain silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material.

2. The preparation method of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material according to claim 1, characterized in that, The amount of bismuth nitrate hexahydrate added is 100~120 g / L, the amount of ferric nitrate hexahydrate added is 80~100 g / L, the concentration of KOH solution is 5~7.5 mol / L, and the amount of silver nitrate added is 1wt%~9wt% of the mass of bismuth ferrite nanomaterials.

3. The preparation method of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material according to claim 1, characterized in that, The conditions for the hydrothermal reaction include: hydrothermal reaction at 140~160℃ for 4~6 hours.

4. The preparation method of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material according to claim 1, characterized in that, The duration of ultraviolet irradiation is 1 to 3 hours.

5. The preparation method of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material according to claim 1, characterized in that, The drying conditions were all: drying at 100~120℃ for 8~12 hours.

6. The preparation method of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material according to claim 1, characterized in that, The calcination conditions are: calcination at 200~400℃ for 2~4 hours.

7. A silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, characterized in that, The silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material was prepared using any one of claims 1 to 6.

8. The silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material according to claim 7, characterized in that, The silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material is a rod-shaped structure encapsulated in nanosheets, Ag + The silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material, uniformly doped in the BiFeO3 lattice, has a particle size of 8~30 μm.

9. The application of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material according to claim 7 or 8 in the preparation of Staphylococcus aureus antibacterial agents or Escherichia coli antibacterial agents.

10. The application of the silver-doped bismuth ferrite nanocomposite piezoelectric antibacterial material according to claim 7 or 8 in the preparation of medical protective materials, antibacterial coatings or water purification materials.

Citation Information

Patent Citations

  • Self-assembled lanthanum cobaltate microsphere / silver phosphate nano-composite photo-responsive antibacterial agent as well as preparation method and application of self-assembled lanthanum cobaltate microsphere / silver phosphate nano-composite photo-responsive antibacterial agent

    CN116060050A

  • A g-C3N4 / LaCoO3 / Co3O4 ternary nanocomposite antibacterial agent and its preparation method and application

    CN116212921B